Les éthiques environnementales aux bords du politique. Esquisse d'un perfectionnisme écocentrique - Rémi Beau (Éditions en environnement VertigO, 2020)
Since the non-anthropocentric environmental ethics hardly fit in the traditional categories of liberal political thought, they did not succeed in establishing on a political ground. As a matter of fact, the research on ecological democracy has rarely taken inspiration from environmental ethics. Nevertheless, the recent thoughts on democracy as a form of life spread a new light on the contribution of an ecocentric ethics to the political thought. This contribution is revealed by the study of the ordinary practices of reproducing the daily life and maintaining the community. In light of the dialogue between Henry David Thoreau and Baird Callicott, I highlight the way a democratic definition of the relationships between the individuals and their socio-ecological communities calls for the development of an ecocentric perfectionism.